Quantification of Persistence of Escherichia coli O157:H7 in Contrasting Soils - A. Mark Ibekwe; Sharon K. Papiernik; Catherine M. Grieve; Ching-Hong Yang (International Journal of Microbiology)
Persistence of Escherichia coli (E. coli) O157:H7 in the environment is a major concern to vegetable and fruit growers where farms and livestock production are in close proximity. The objectives were to determine the effects of preplant fumigation treatment on the survival of E. coli O157:H7 in two soils and the effects of indigenous bacterial populations on the survival of this pathogen. Real-time PCR and plate counts were used to quantify the survival of E. coli O157:H7 in two contrasting soils after fumigation with methyl bromide (MeBr) and methyl iodide (MeI). Ten days after fumigation, E. coli O157:H7 counts were significantly lower (𝑃=.0001) in fumigated soils than in the non-fumigated. Direct comparison between MeBr and MeI within each soil indicated that these two fumigants showed similar impacts on E. coli O157:H7 survival. Microbial species diversity as determined by DGGE was significantly higher in clay soil than sandy soil and this resulted in higher initial decline in population in clay soil than in sandy soil. This study shows that if soil is contaminated with E. coli O157:H7, fumigation alone may not eliminate the pathogen, but may cause decrease in microbial diversity which may enhance the survival of the pathogen.